PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA SMP MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) BAGI SISWA BERKEBUTUHAN KHUSUS - Fandi Mamonto; Masri Kudrat Umar; Dewi Diana Paramata (Universitas Negeri Gorontalo, 2021)
This study aims to produce a science learning device for junior high school students using a cooperative model type Student Teams Achievement Divisions (STAD) for students with special needs that are valid and fit for use theoretically. The research method used is the development of the 4D model design through 4 stages including the defining stage, the design stage, the development stage, and the dissemination stage. The technique of collecting data through validation sheets consists of lecturers, science teachers, school principals, and students. Based on the research results, the validity of the equipment was obtained through the Aiken V index in the RPP of 0.89, LKPD of 0.88, and THB of 0.88. The three components of the device are considered very valid criteria. The reliability test of each component for RPP is 0.818, LKPD is worth. 0.857, and THB worth 0.884. The components of learning equipment are reliable with good categories based on the Interrater Correlation Coefficient (ICC). Theoretically, the learning tools developed are valid and feasible to be tested in class VIII of the Gorontalo City Learning Activity Center (SKB).